An Examination of Personality Traits Associated with Autonomous Sensory Meridian Response (ASMR) - Fredborg, Beverley; Clark, Jim; Smith, Stephen D. (Frontiers in Psychology, 2017)
Autonomous Sensory Meridian Response (ASMR) is a perceptual condition in which the presentation of particular audio-visual stimuli triggers intense, pleasurable tingling sensations in the head and neck regions, which may spread to the periphery of the body. These triggering stimuli are often socially intimate in nature, and usually involve repetition of movements and/or sounds (e.g., hearing whispering, watching someone brush her hair). Reports of ASMR experiences first appeared in online communities in 2010; since this time, these communities have expanded, with some groups consisting of over 100,000 members. However, despite the apparent prevalence of ASMR, there is currently no research on the personality characteristics that co-occur with this condition. In the current study, 290 individuals with ASMR and 290 matched controls completed the Big Five Personality Inventory (BFI; John, Donahue, & Kentle, 1999); participants with ASMR also completed a questionnaire related to their ASMR phenomenology. Individuals with ASMR demonstrated significantly higher scores on Openness-to-Experience and Neuroticism, and significantly lower levels of Conscientiousness, Extraversion, and Agreeableness compared to matched controls. Further, ratings of subjective ASMR intensity in response to 14 common ASMR stimuli were positively correlated with the Openness-to-Experience and Neuroticism dimensions of the BFI. These results provide preliminary evidence that ASMR is associated with specific personality traits and suggest avenues for further investigation.